BERLIN AS A CREATIVE FIELD: DECONSTRUCTING THE ROLE OF THE URBAN CONTEXT IN CREATIVE PRODUCTION - Copercini, Marco (Quaestiones Geographicae, 2016)
The relation between creative activities and the cities in which they are concentrated is that of mutual influence and dependence. This kind of dynamics is well described by the concept of the creative field by Scott (2006, 2008, 2010, 2014). According to this concept, there is a shared relational context among creative actors in a given place, as well as between them and the local socio-economic-institutional context. Consequently, the economic profile and innovation capacity of a city are determined by the main sectors based there. In this paper, I discuss the role of the creative field in developing the relation between the city of Berlin and creative actors of the fashion design sector, as well as elements of the creative field that are considered relevant by fashion designers in their creative work. This perspective allows the underscoring of some relevant drivers that have made Berlin one of the most relevant places for fashion design in Germany and the whole of Europe. This research has been supported by administrative data from the period 1990–2015, along with personal interviews in the fashion design sector. Shown are not only the existing relations between the urban context and the creative activities of designers, but also how the development of the creative field of the city might be influenced. Consequently, the creative work of fashion designers and their location decisions have to be considered in relation to the creative field as a dynamic combination of variable elements that influence, and are influenced by, each other.